Insulin affects synaptosomal GABA and glutamate transport under oxidative stress conditions - Duarte, Ana Isabel (2003)
In this study, we investigated the in vitro effect of exogenously administered insulin on the susceptibility to oxidative stress and on the accumulation of the amino acid neurotransmitters [gamma]-aminobutyric acid (GABA) and glutamate in a synaptosomal fraction isolated from male Wistar rat brain cortex. Insulin (1 [mu]M) did not affect synaptosomal lipid peroxidation induced by the oxidant pair ascorbate/Fe2+, although under these conditions an increase in thiobarbituric acid reactive substances (TBARS) levels was observed. Under control conditions, the presence of insulin did not change the uptake of [3H]GABA or [3H]glutamate. In contrast, under oxidizing conditions, we observed a 1.8- and a 2.2-fold decrease in [3H]GABA and [3H]glutamate accumulation, respectively, and insulin reverted the lower levels of both [3H]GABA and [3H]glutamate accumulation (to 86.74±6.26 and 67.01±6.65% of control, respectively). Insulin also increased the extrasynaptosomal levels of GABA and glutamate, determined both in control and oxidizing conditions. From this study, we can conclude that insulin is a modulator of amino acid neurotransmitter transport, either directly, as seems to occur under normal conditions, or via the decrease in ATP levels and the subsequent reversion of the amino acid transporters, as seems to occur under oxidative stress conditions. The modulation of both GABA and glutamate transport might be implicated in the neuroprotective role of insulin.